Total mercury concentrations in invasive lionfish (Pterois volitans/miles) from the Atlantic coast of Florida. - Eric G Johnson; Angelina Dichiera; Danielle Goldberg; MaryKate Swenarton; James Gelsleichter (PLoS ONE)
Invasive lionfish (Pterois volitans/miles) pose a serious threat to marine ecosystems throughout the western Atlantic Ocean and Caribbean Sea. The development of a fishery for lionfish has been proposed as a strategy for controlling populations; however, there is concern about consumption of this species by humans due to its high trophic position and potential for bioaccumulation of mercury. We analyzed total mercury (THg) in tissues of lionfish from two locations on the east coast of Florida. THg in lionfish increased with size and differed by location and sex. THg was highest in muscle tissue and was strongly positively correlated among tissues. THg in lionfish was lower than other commonly consumed marine fishes, and falls into Florida's least restrictive advisory level. Consumption of lionfish poses a low risk and concerns over mercury bioaccumulation should not present a significant barrier to lionfish harvest.